Worthington Glacier, Alaska scale 1:10,000 / prepared by James B. Case at the Institute of Geodesy, Photogrammetry, and Cartography, the Ohio State University under the American Geographical Society's IGY Project 4.11 - Ohio State University (American Geographical Society of New York, 1958)
Blueline print.; Relief shown by contours and spot heights.; North oriented to the upper right.; Folded into "IGY Project 4.11 report no. 7 map of the Worthington Glacier, Chugach Mountains, Alaska" by James B. Case, October 1958. Color 1:10,000